Recombination Rate of D Atoms in Solid D2 in the Temperature Range from 0.23 to 1.64 K - Wetzel, C. K.; Lee, D. M.; Sheludiakov, S.; Ahokas, J.; Vasiliev, S.; Khmelenko, V. V. (Springer Nature, 2026)
The recombination rates of D atoms in solid D2 films were measured in the temperature range 0.23–1.64 K. Atoms were formed in thin D2 films by maintaining radio-frequency discharge above the film surface for several days. After stopping discharge the decay of D atoms concentrations was monitored at different temperatures by the method of electron spin resonance (ESR). Decreasing the films temperature from 1.64 to 0.23 K resulted in reducing the recombination rate from 7.2 × 10−26 cm3s−1 to 1.0 × 10−27 cm3s−1.